From ear to body: the auditory-motor loop in spatial cognition - Viaud-Delmon, Isabelle; Warusfel, Olivier (Frontiers in Neuroscience, 2014)
Spatial memory is mainly studied through the visual sensory modality: navigation tasks in humans rarely integrate dynamic and spatial auditory information. In order to study how a spatial scene can be memorized on the basis of auditory and idiothetic cues only, we constructed an auditory equivalent of the Morris water maze, a task widely used to assess spatial learning and memory in rodents. Participants were equipped with wireless headphones, which delivered a soundscape updated in real time according to their movements in 3D space. A wireless tracking system (video infrared with passive markers) was used to send the coordinates of the subject's head to the sound rendering system. The rendering system used advanced HRTF-based synthesis of directional cues and room acoustic simulation for the auralization of a realistic acoustic environment. Participants were guided blindfolded in an experimental room. Their task was to explore a delimitated area in order to find a hidden auditory target, i.e., a sound that was only triggered when walking on a precise location of the area. The position of this target could be coded in relationship to auditory landmarks constantly rendered during the exploration of the area. The task was composed of a practice trial, 6 acquisition trials during which they had to memorize the localization of the target, and 4 test trials in which some aspects of the auditory scene were modified. The task ended with a probe trial in which the auditory target was removed. The configuration of searching paths allowed observing how auditory information was coded to memorize the position of the target. They suggested that space can be efficiently coded without visual information in normal sighted subjects. In conclusion, space representation can be based on sensorimotor and auditory cues only, providing another argument in favor of the hypothesis that the brain has access to a modality-invariant representation of external space.